2011
DOI: 10.1002/jnr.22760
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the expression of N‐methyl‐D‐aspartate receptors in the nucleus tractus solitarii induces antinociception and increases blood pressure

Abstract: N-methyl-D-aspartate receptors (NMDAR) have a role in cardiovascular control at the nucleus tractus solitarii (NTS), eliciting increases or decreases in blood pressure (BP), depending on the area injected with the agonists. In spite of the association between cardiovascular control and pain modulation, the effects of manipulating NMDAR in pain responses have never been evaluated. In this study, we decreased the expression of NMDAR in the NTS using gene transfer to target receptor subunits and evaluate long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…; Marques‐Lopes et al . ). However, the specific mechanism(s) by which they contribute to the fidelity of transmission across afferent–NTS neuron synapses are not well understood.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Marques‐Lopes et al . ). However, the specific mechanism(s) by which they contribute to the fidelity of transmission across afferent–NTS neuron synapses are not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…; Marques‐Lopes et al . ). Consistent with our model, NMDA‐R antagonists only attenuate aortic baroreceptor reflexes initiated by high frequency afferent discharge, while AMPA‐Rs contribute to responses mediated by both low and high afferent discharge (Gordon & Leone, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The medullar (NST and A1) populations are positioned to relay sensory, visceral, cardiorespiratory and nociceptive information between the peripheral and central nervous systems [46; 49]. Studies have found a role for the NST in the baroreflex to noxious thermal stimulation [22] and in the tonic control of nociceptive thresholds [32]. Furthermore, medullar catecholamine neurons are activated by visceral pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…The 1-week time point was chosen based on previous reports showing that the human synapsin promoter is fully active at this time 22,28,56 and taking into account the time necessary for the retrograde transport of CTb from the DRt to its brain afferents. 1 …”
Section: Cannula Implantationmentioning
confidence: 99%